Reduction of Graphene Oxide: Controlled Synthesis by Microwave Irradiation - Endah Fitriani Rahayu; Bunnari Bunnari; Andri Hardyansyah (Universitas Jenderal Soedirman, 2020)
Graphene has been attracting enormous attention in the scientific community because of its unique properties and use for various applications. Graphene has been synthesized in various ways, one of which is the graphite oxidation method to form graphene oxide (GO). Reduction of GO to reduced graphene oxide (RGO) is necessary to recover the conjugated network and electrical conductivity, and for this research, this was achieved using microwave irradiation. Microwave synthesis provides an alternative method, saving more time in the reaction process. In this research, graphene was synthesized from graphite by the modified Hummers method and microwave irradiation. This research proves that graphene can be synthesized with a high-quality structure and in a shorter amount of time using microwave irradiation to reduce GO. With longer microwave exposure, less GO is present in the sample, as indicated by the absence of an n–π* electronic transition in the absorbance graph and the absence of oxide groups in the Fourier-Transform Infra-Red spectrum. With increasing microwave power, the reduction process is short-lived, and better quality RGO is produced. This study shows that the new reduction process occurs within 20 minutes with a power of 450 and 630 watts, but at 900 watts, the reduction of GO occurs within 10 minutes, as shown by UV-Vis and FTIR spectra.